ANALYSIS OF THE PROPERTIES OF OUTPUT SIGNALS OF AUTOMATED ACTIVE POWER CONTROL OF ELECTRIC DRILL ENGINES - Шавранський, Михайло; Дмитрик, Тарас (SWorldJournal, 2024)
The paper will carry out a comprehensive analysis of the parameters of the output signals, including frequency, amplitude, time characteristics and other key indicators. The results of this study will contribute to the further improvement of automated co